A novel mutation in the TUBB8 gene is associated with complete cleavage failure in fertilized eggs - Yuan, Ping; Zheng, Lingyan; Liang, Hao; Li, Yu; Zhao, Haijing; Li, Ruiqi; Lai, Luhua; Zhang, Qingxue; Wang, Wenjun (Journal of assisted reproduction and genetics, 2018)
Purpose Cleavage of the zygote during human reproduction is a key event of early embryonic development. The genetic events associated with idiopathic embryonic cleavage failure are not certain. Mutations in the tubulin beta 8 class VIII ( TUBB8 ) gene have been reported to be associated with oocyte maturation, fertilization, and developmental arrest. Here, we aimed to assess the clinical and genetic characteristics of complete cleavage failure in fertilized eggs. Methods We have characterized a patient with a 9-year history of primary infertility in a non-consanguineous family from China. The patient presented complete cleavage failure in all two-pronuclear (2PN) fertilized oocytes after 2 cycles of in vitro fertilization (IVF). We performed Sanger sequencing of the TUBB8 gene in the patient, and further bioinformatics analysis to identify pathogenesis of gene. Results A novel homozygous mutation, c.322G > A (p.Glu108Lys), was detected, and this change was absent from 179 control subjects. Glutamic acid is highly conserved at this position, and replacement by lysine was predicted to be repelled by the α-tubulin positive region, disrupting the α-β tubulin interaction. Conclusions Our findings presented a homozygous mutation of TUBB8 associated with complete cleavage failure in fertilized eggs and provided new data for the genotype-phenotype of TUBB8 -related diseases.